(untitled) (Global Journal of Management and Business Research, 2019)
The audit process is the process of continuously collecting audit evidence. Audit evidence is processed when auditors are doing financial audits. Generally speaking, audit evidence shall be both reliable and relevant. Auditors exam evidence available from various sources to decrease the probability of material misstatement and audit failure (Bell, Peecher, and Solomon, 2005). This paper elaborates on the definition of audit evidence, classification of audit evidence, and techniques of collecting audit evidence in China and the United States. On this basis, the paper then compares the differences between the definition, classification and, collection of audit evidence in China and the United States. We used the method of comparison and analysis. In general, China and the US have the same concepts in audit evidence. They both defined the sufficiency and appropriateness of audit evidence to draw an audit opinion (Audit Evidence: Meaning, Definition, and Importance). China and the US have a different emphasis on audit evidence classification. China and the US have most audit evidence collection techniques in the same. China more emphasize the collection technique of supervision besides observation (The Central People’s Government of the People’s Republic of China, 2004), while the US listed reperformance as one of its most significant collection techniques (Audit evidence: Definition, Type, Procedures, and Quality). China and the US have the same expressions, both of which are "adequate and appropriate" and state that auditors must obtain sufficient evidence.